Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which of the matrices [tex]\( B \)[/tex] satisfies the equation [tex]\( AB = I \)[/tex] for a given matrix [tex]\( A \)[/tex], we need to check each candidate matrix [tex]\( B \)[/tex] and verify that the product [tex]\( AB \)[/tex] yields the identity matrix.
Given:
[tex]\[ A = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \][/tex]
The candidate matrices are:
[tex]\[ B_1 = \begin{bmatrix} \frac{1}{4} & 1 \\ -\frac{3}{4} & -2 \end{bmatrix} \][/tex]
[tex]\[ B_2 = \begin{bmatrix} -\frac{1}{4} & -1 \\ \frac{3}{4} & 2 \end{bmatrix} \][/tex]
[tex]\[ B_3 = \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
We need to calculate the matrix products [tex]\( AB_1 \)[/tex], [tex]\( AB_2 \)[/tex], and [tex]\( AB_3 \)[/tex], and see which one equals the [tex]\( 2 \times 2 \)[/tex] identity matrix [tex]\( I \)[/tex]:
[tex]\[ I = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} \][/tex]
### Checking [tex]\( AB_1 \)[/tex]:
[tex]\[ AB_1 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} \frac{1}{4} & 1 \\ -\frac{3}{4} & -2 \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot \frac{1}{4} + 4 \cdot -\frac{3}{4} = -\frac{1}{4} - 3 = -\frac{1}{4} - \frac{12}{4} = -\frac{13}{4} \\ (1,2) & : -1 \cdot 1 + 4 \cdot -2 = -1 - 8 = -9 \\ (2,1) & : -3 \cdot \frac{1}{4} + 8 \cdot -\frac{3}{4} = -\frac{3}{4} - 6 = -\frac{3}{4} - \frac{24}{4} = -\frac{27}{4} \\ (2,2) & : -3 \cdot 1 + 8 \cdot -2 = -3 - 16 = -19 \\ \end{align*} \][/tex]
Since [tex]\( AB_1 \neq I \)[/tex], [tex]\( B_1 \)[/tex] is not the correct matrix.
### Checking [tex]\( AB_2 \)[/tex]:
[tex]\[ AB_2 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} -\frac{1}{4} & -1 \\ \frac{3}{4} & 2 \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot -\frac{1}{4} + 4 \cdot \frac{3}{4} = \frac{1}{4} + 3 = \frac{1}{4} + \frac{12}{4} = \frac{13}{4} \\ (1,2) & : -1 \cdot -1 + 4 \cdot 2 = 1 + 8 = 9 \\ (2,1) & : -3 \cdot -\frac{1}{4} + 8 \cdot \frac{3}{4} = \frac{3}{4} + 6 = \frac{3}{4} + \frac{24}{4} = \frac{27}{4} \\ (2,2) & : -3 \cdot -1 + 8 \cdot 2 = 3 + 16 = 19 \\ \end{align*} \][/tex]
Since [tex]\( AB_2 \neq I \)[/tex], [tex]\( B_2 \)[/tex] is not the correct matrix.
### Checking [tex]\( AB_3 \)[/tex]:
[tex]\[ AB_3 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot -2 + 4 \cdot -\frac{3}{4} = 2 - 3 = -1 \\ (1,2) & : -1 \cdot 1 + 4 \cdot \frac{1}{4} = -1 + 1 = 0 \\ (2,1) & : -3 \cdot -2 + 8 \cdot -\frac{3}{4} = 6 - 6 = 0 \\ (2,2) & : -3 \cdot 1 + 8 \cdot \frac{1}{4} = -3 + 2 = -1 \\ \end{align*} \][/tex]
Thus:
[tex]\[ \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} = I \][/tex]
So [tex]\( AB_3 = I \)[/tex], which means that the correct matrix [tex]\( B \)[/tex] is:
[tex]\[ \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
Therefore, the correct value of [tex]\( B \)[/tex] is:
[tex]\[ \boxed{\begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix}} \][/tex]
Given:
[tex]\[ A = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \][/tex]
The candidate matrices are:
[tex]\[ B_1 = \begin{bmatrix} \frac{1}{4} & 1 \\ -\frac{3}{4} & -2 \end{bmatrix} \][/tex]
[tex]\[ B_2 = \begin{bmatrix} -\frac{1}{4} & -1 \\ \frac{3}{4} & 2 \end{bmatrix} \][/tex]
[tex]\[ B_3 = \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
We need to calculate the matrix products [tex]\( AB_1 \)[/tex], [tex]\( AB_2 \)[/tex], and [tex]\( AB_3 \)[/tex], and see which one equals the [tex]\( 2 \times 2 \)[/tex] identity matrix [tex]\( I \)[/tex]:
[tex]\[ I = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} \][/tex]
### Checking [tex]\( AB_1 \)[/tex]:
[tex]\[ AB_1 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} \frac{1}{4} & 1 \\ -\frac{3}{4} & -2 \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot \frac{1}{4} + 4 \cdot -\frac{3}{4} = -\frac{1}{4} - 3 = -\frac{1}{4} - \frac{12}{4} = -\frac{13}{4} \\ (1,2) & : -1 \cdot 1 + 4 \cdot -2 = -1 - 8 = -9 \\ (2,1) & : -3 \cdot \frac{1}{4} + 8 \cdot -\frac{3}{4} = -\frac{3}{4} - 6 = -\frac{3}{4} - \frac{24}{4} = -\frac{27}{4} \\ (2,2) & : -3 \cdot 1 + 8 \cdot -2 = -3 - 16 = -19 \\ \end{align*} \][/tex]
Since [tex]\( AB_1 \neq I \)[/tex], [tex]\( B_1 \)[/tex] is not the correct matrix.
### Checking [tex]\( AB_2 \)[/tex]:
[tex]\[ AB_2 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} -\frac{1}{4} & -1 \\ \frac{3}{4} & 2 \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot -\frac{1}{4} + 4 \cdot \frac{3}{4} = \frac{1}{4} + 3 = \frac{1}{4} + \frac{12}{4} = \frac{13}{4} \\ (1,2) & : -1 \cdot -1 + 4 \cdot 2 = 1 + 8 = 9 \\ (2,1) & : -3 \cdot -\frac{1}{4} + 8 \cdot \frac{3}{4} = \frac{3}{4} + 6 = \frac{3}{4} + \frac{24}{4} = \frac{27}{4} \\ (2,2) & : -3 \cdot -1 + 8 \cdot 2 = 3 + 16 = 19 \\ \end{align*} \][/tex]
Since [tex]\( AB_2 \neq I \)[/tex], [tex]\( B_2 \)[/tex] is not the correct matrix.
### Checking [tex]\( AB_3 \)[/tex]:
[tex]\[ AB_3 = \begin{bmatrix} -1 & 4 \\ -3 & 8 \end{bmatrix} \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
Calculating the elements:
[tex]\[ \begin{align*} (1,1) & : -1 \cdot -2 + 4 \cdot -\frac{3}{4} = 2 - 3 = -1 \\ (1,2) & : -1 \cdot 1 + 4 \cdot \frac{1}{4} = -1 + 1 = 0 \\ (2,1) & : -3 \cdot -2 + 8 \cdot -\frac{3}{4} = 6 - 6 = 0 \\ (2,2) & : -3 \cdot 1 + 8 \cdot \frac{1}{4} = -3 + 2 = -1 \\ \end{align*} \][/tex]
Thus:
[tex]\[ \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} = I \][/tex]
So [tex]\( AB_3 = I \)[/tex], which means that the correct matrix [tex]\( B \)[/tex] is:
[tex]\[ \begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix} \][/tex]
Therefore, the correct value of [tex]\( B \)[/tex] is:
[tex]\[ \boxed{\begin{bmatrix} -2 & 1 \\ -\frac{3}{4} & \frac{1}{4} \end{bmatrix}} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.